The Fortunes and Misfortunes of the Famous Moll Flanders - Defoe, Daniel, 1661?-1731 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Fortunes and Misfortunes of the Famous Moll Flanders" by Daniel Defoe is a novel published in 1722. Born in prison to a convict mother, Moll navigates survival through a series of marriages, deceptions, and reinventions. As circumstances strip away her security time and again, she transforms from hopeful young woman to skilled con artist to accomplished thief. Through cunning and charm, Moll pursues the one thing that eludes her: lasting prosperity and peace in a world that offers women few honest paths to independence. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Moll_Flanders
Release date is 1995-12-01
Keywords: London (England) -- Fiction; Picaresque literature; Adventure stories; Criminals -- Fiction; Prostitutes -- Fiction; Children of prisoners -- Fiction; British -- Virginia -- Fiction; Women -- England -- Fiction; Repentance -- Fiction; Virginia -- Fiction